A case series of persistent lymphopaenia following treatment with fumaric acid esters for psoriasis. (11th January 2021) - Beatty, Paula Evelyn; Killion, Lisa; Callaghan, Grainne; Tierney, Emma; Kelly, Genevieve; Tobin, Anne Marie
Abstract: What is known and objective: Fumaric acid esters (FAEs) have been used for fifty years to treat moderate‐to‐severe psoriasis. However, recent case reports of progressive multifocal leukoencephalopathy, associated with FAE‐induced lymphopaenia, have been a cause for concern (J Dtsch Dermatol Ges. 2009;7:603). Case series: We report six cases of persistent lymphopaenia following cessation of treatment with FAEs, with a mean duration of lymphopaenia of 33 months. What is new and conclusion: Given the lack of evidence regarding expected recovery of lymphocyte counts, further research is required to guide physicians in the risk stratification of patients prior to considering treatment with FAEs.